(untitled) (Applied Biological Research, 2023)
Prolapse of genitalia is one of the common reproductive disorders in buffaloes and several other species. Cervico-vaginal prolapse is a maternal abnormality in buffalo observed most commonly during last 2 to 3 months of pregnancy but may occur after parturition and can be noticed by the protrusion of varying parts of vaginal wall and cervix through exposed vulva (Noakes et al., 2009). Protrusion of complete cervix and vagina through vulva is a general condition in pluriparous cows although the exact cause of disorder has not been ascertained (Morrow, 1986). In some conditions, urinary bladder is trapped within the prolapsed part leading to further enlargement and complications (Youngquist and Threlfall, 2007). This is considered as an emergency condition and should be attended prior to unnecessary contamination followed by infection, too much edema, mucosal trauma and hemorrhages. In present study, a case of post-partum cervico-vaginal prolapse in a pluriparous ‘Murrah’ buffalo and its successful treatment is reported.